2014
DOI: 10.1166/jnn.2014.8777
|View full text |Cite
|
Sign up to set email alerts
|

Probing Actin Filament and Binding Protein Interaction Using an Atomic Force Microscopy

Abstract: Actin filaments play essential roles in many kinds of cellular functions by interacting with hundreds of actin binding proteins. Here we probe the interaction between actin filament and a binding protein, α-actinin, using an atomic force microscopy (AFM) and dynamic force spectroscopy (DFS). The distribution of rupturing events including specific and non-specific interactions of actin filament/α- actinin and BSA/α-actinin were analyzed. The rupture force of the actin filament/α-actinin binding was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These pairs include an anticancer peptide fragment of azurin (a bacterial protein that can be internalized in cancer cells and induce apoptosis) with p53, 28 p53 with Mdm2, 29 ribonuclease barnase with its inhibitor barstar, 30 and actin filament and binding protein. 31 Bonazza and co-workers also utilized AFM to investigate the complex formation between the von Willebrand factor (VWF) and factor VIII (FVIII), two essential hemostatic components of human blood. 32 Their results indicated that the fraction of VWF knots bound to FVIII was 25 ± 4%, and declined to 2 ± 1% when a complex was formed in the presence of the high salt buffer containing 500 mM Ca 2+ (Figure 3).…”
Section: Experimental Research Progressmentioning
confidence: 96%
See 1 more Smart Citation
“…These pairs include an anticancer peptide fragment of azurin (a bacterial protein that can be internalized in cancer cells and induce apoptosis) with p53, 28 p53 with Mdm2, 29 ribonuclease barnase with its inhibitor barstar, 30 and actin filament and binding protein. 31 Bonazza and co-workers also utilized AFM to investigate the complex formation between the von Willebrand factor (VWF) and factor VIII (FVIII), two essential hemostatic components of human blood. 32 Their results indicated that the fraction of VWF knots bound to FVIII was 25 ± 4%, and declined to 2 ± 1% when a complex was formed in the presence of the high salt buffer containing 500 mM Ca 2+ (Figure 3).…”
Section: Experimental Research Progressmentioning
confidence: 96%
“…Moreover, the recognition events between ligand–receptor pairs have been investigated for understanding the physiological roles of these biological proteins at molecular level. These pairs include an anticancer peptide fragment of azurin (a bacterial protein that can be internalized in cancer cells and induce apoptosis) with p53, p53 with Mdm2, ribonuclease barnase with its inhibitor barstar, and actin filament and binding protein …”
Section: Experimental Research Progressmentioning
confidence: 99%
“…There are many methods to study PPIs, such as the most commonly used immunoprecipitation (IP) [ 13 ], tandem affinity purification-mass spectrometry (TAP-MS) [ 14 ], and the pull-down experiment that is increasingly favored by researchers [ 15 ]. In addition, fluorescence resonance energy transfer (FRET), surface plasmon resonance (SPR), and optical tweezers are widely used in this research field [ 16 , 17 , 18 ]. For nanoscale protein assay experiments, AFM is a very powerful tool because it uses AFM tips modified with biomolecules to measure interactions with receptors.…”
Section: Introductionmentioning
confidence: 99%